2021
DOI: 10.3390/cryst11080923
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effects of Grain Boundary on Deformation Behavior of Bicrystalline Pillar by Crystal Plasticity Finite Element Method

Abstract: A dislocation density–grain boundary interaction scheme coupled with the dislocation density-based crystalline plasticity finite element method has been established and used to investigate the deformation behavior of bicrystalline pillars with the same grain boundary misorientation angle but different crystal orientations. It is found that the angle between the activated slip systems, which is determined by the crystal orientations, rather than the grain boundary misorientation angle, influences the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It is considered that the increase of grain size and the decrease of DDC resistance are related to strain concentration at grain boundary during tension. For grain boundary without precipitates, sliding of grain boundary during tension leads to stress concentration and strain localization at trigeminal grain boundary [3,7]. With the increase of grain size, each trigeminal grain boundary needs to bear greater stress concentration and strain.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is considered that the increase of grain size and the decrease of DDC resistance are related to strain concentration at grain boundary during tension. For grain boundary without precipitates, sliding of grain boundary during tension leads to stress concentration and strain localization at trigeminal grain boundary [3,7]. With the increase of grain size, each trigeminal grain boundary needs to bear greater stress concentration and strain.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…On the other hand, small grain size and more curved grain boundary of 305 sample also affects its VoA. Through finite element calculation, Zhou Hui [7] found that the maximum Mises stress of curved grain boundary is reduced and the stress Engineering Materials Research distribution is more uniform than that of straight grain boundary. In terms of macro properties, 305 sample has stronger grain boundary deformation ability and higher VoA than that of 315.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steels and iron-based alloys [2-9]; • Non-ferrous alloys with fcc-(Ni- [10,11] and Cu-based [12][13][14]), or hcp crystal structure (Mg- [15,16] and Ti-based [17,18]). Other examples include Zirconium [19], Bi-Sn alloy [20] or polycarbonate resins [21]; • Multicomponent and high-entropy alloys [22][23][24]; • General theoretical studies on crystal plasticity [25][26][27].…”
mentioning
confidence: 99%